S100B chaperone multimers suppress the formation of oligomers during Aβ42 aggregation - Figueira, António J.; Saavedra, Joana; Cardoso, Isabel; Gomes, Cláudio M. (Frontiers in Neuroscience, 2023)
Extracellular aggregation of the amyloid-β 1–42 (Aβ42) peptide is a major hallmark of Alzheimer’s disease (AD), with recent data suggesting that Aβ intermediate oligomers (AβO) are more cytotoxic than mature amyloid fibrils. Understanding how chaperones harness such amyloid oligomers is critical toward establishing the mechanisms underlying regulation of proteostasis in the diseased brain. This includes S100B, an extracellular signaling Ca2+-binding protein which is increased in AD as a response to neuronal damage and whose holdase-type chaperone activity was recently unveiled. Driven by this evidence, we here investigate how different S100B chaperone multimers influence the formation of oligomers during Aβ42 fibrillation. Resorting to kinetic analysis coupled with simulation of AβO influx distributions, we establish that supra-stoichiometric ratios of dimeric S100B-Ca2+ drastically decrease Aβ42 oligomerization rate by 95% and AβO levels by 70% due to preferential inhibition of surface-catalyzed secondary nucleation, with a concomitant redirection of aggregation toward elongation. We also determined that sub-molar ratios of tetrameric apo-S100B decrease Aβ42 oligomerization influx down to 10%, while precluding both secondary nucleation and, more discreetly, fibril elongation. Coincidently, the mechanistic predictions comply with the independent screening of AβO using a combination of the thioflavin-T and X-34 fluorophores. Altogether, our findings illustrate that different S100B multimers act as complementary suppressors of Aβ42 oligomerization and aggregation, further underpinning their potential neuroprotective role in AD.